APPLICATION OF SAVI LEARNING APPROACH TO IMPROVE LEARNING CONCENTRATION AND ACHIEVEMENT (Studies on Social Sciences Subjects for Class VIII Students of MTsN 1 Bengkulu Selatan) - Yulia Hadiyanti; Alexon Alexon (UNIB Press, 2018)
This research purpose are to improve concentration and learning achievement of the implementation of SAVI approaches. The method used in this research is a classroom action research and quasi experiment. Research subjects for classroom action research were students of class VIIIA amounted to 18 students and the population in this study were 36 students consisting of grade VIIIB amounted to 18 students as kuasi-experiment class and VIIIC which amounted to 18 students as control class. Technique of collecting data used is using observation and test. The data obtained were analyzed by using the mean formula and dependent and independent sample t test. The results showed that the application of SAVI approaches improves students' concentration and learning achievement. The implication of the implementation of learning, the teacher must be serious and master the learning SAVI approach. Based on the result of the study the effective learning approach can improve learning achievement so that it can be applied to other classes or schools. The existence of this research is expected to be able to provide benefits to the world of education for students, teachers and schools.